2022
DOI: 10.1021/acs.molpharmaceut.2c00070
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Tumor Cells and Receptor-Ligand Simulation Models for the Development of PET Imaging Probes Targeting PSMA and GRPR and a Possible Crosstalk between the Two Receptors

Abstract: Prostate-specific membrane antigen (PSMA) and gastrin-releasing peptide receptor (GRPR) have both been used in nuclear medicine as targets for molecular imaging and therapy of prostate (PCa) and breast cancer (BCa). Three bioconjugate probes, the PSMA specific: [ 68 Ga]Ga-1, ((HBED-CC)-Ahx-Lys-NH-CO-NH Glu or PSMA-11), the GRPR specific: [ 68 Ga]Ga-2, ((HBED-CC)-4-amino-1-carboxymethyl piperidine-[D-Phe 6 , Sta 13 ]BN(6−14), a bombesin (BN) analogue), and 3 (the BN analogue: 4-amino-1-carboxymethyl piperidine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…In the study conducted by Liolios et al [ 28 ], the prostate-specific membrane antigen (PSMA) and gastrin-releasing peptide receptor (GRPR) were considered as valuable biological targets for the molecular imaging and therapy of prostate (PCa) and breast (BCa) cancer. They both are widely expressed on the surfaces of PCa cells and BCa cells during the progression of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Liolios et al [ 28 ], the prostate-specific membrane antigen (PSMA) and gastrin-releasing peptide receptor (GRPR) were considered as valuable biological targets for the molecular imaging and therapy of prostate (PCa) and breast (BCa) cancer. They both are widely expressed on the surfaces of PCa cells and BCa cells during the progression of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The surface bound fraction of radioactivity was always higher for the IONs-BN compared to the internalized fraction, at both temperatures studied, indicating that the BN pharmacophore has changed their internalization process and that the IONs-BN have the same behavior as the BN antagonist. The BN antagonists are known for showing minimal internalization and for being mainly surface bound on PC3 cells (36,54,55). Moreover, in most cases, the internalized radioactivity reached a plateau at the highest concentrations studied (4 and 5 μg/ml), indicating a saturation in the process.…”
Section: Cell Binding Studiesmentioning
confidence: 91%
“…The docking poses of the PSMA-617 part or the RM2 part of the heterodimer (3) into the binding area of PSMA receptor or BBR2 were performed as previously described in ref. Liolios et al 52 and are shown in Figure 6.…”
Section: Docking Calculationsmentioning
confidence: 97%
“…Considering the increased expression of PSMA in the kidneys, the kidney uptake was much lesser than in other heterodimers we previously developed that ranged between 66-122% IA/g. 51,52 The observed off-targeting uptake in the pancreas was due to the normal expression of GRPRs in this tissue and was gradually degraded with time in a faster rate than the activity located in the tumors. In general, [ 68 Ga]Ga-3 showed dual targeting of PSMA-positive tumors and GRPR-positive tumors and fast clearance from the body, while in comparison to the monomers 2,3 a higher cancer cell-uptake and lower kidneys uptake was observed.…”
Section: Internalizationmentioning
confidence: 99%